Graphene oxide/black phosphorus nanoflake aerogels with robust thermo-stability and significantly enhanced photothermal properties in air. Issue 24 (28th April 2017) - Xing, Chenyang; Jing, Guanghui; Liang, Xin; Qiu, Meng; Li, Zhongjun; Cao, Rui; Li, Xiaojing; Fan, Dianyuan; Zhang, Han
Abstract : Graphene oxide/black phosphorus nanoflake aerogels not only exhibited significantly enhanced photothermal properties but also showed excellent stability. Abstract : Here we report a new kind of three-dimensional (3D) hybrid aerogels, based on graphene oxide (GO) and black phosphorus nanoflakes (BPNFs), for the first time. Our results demonstrate that the as-prepared GO/BPNF hybrid aerogels exhibited significantly enhanced photothermal as well as electrical properties of GO aerogels due to the addition of BP. Moreover, they also possessed excellent photothermal stability under ambient conditions without any protection, which can be ascribed to the coverage of BPNFs with GO nanosheets in these aerogels. This exceptional photothermal property along with robust stability renders GO/BPNF aerogels with promising bio-related applications, such as photothermal therapy for cancer treatment.